Swearing-In Ceremony of New Attorneys Held in Exhibit Hall - Watkins, Howard::::::::: (1981)
Special En Banc session of the local courts: Superior Court Judge Armando Rodriguez; Appellate Court Justices Pauline Davis Franson, Don Franson, Sr., George Brown (Presiding), George Zenovich, Kenneth Andreen, Frederick Stone, and U.S. District Court Judge Myron D. Crocker